2013
DOI: 10.5142/jgr.2013.37.8
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the therapeutic and pharmacological effects of ginseng and ginsenosides in central nervous system

Abstract: Ginseng is one of the most widely used herbal medicines in human. Central nervous system (CNS) diseases are most widely investigated diseases among all others in respect to the ginseng’s therapeutic effects. These include Alzheimer’s disease, Parkinson’s disease, cerebral ischemia, depression, and many other neurological disorders including neurodevelopmental disorders. Not only the various types of diseases but also the diverse array of target pathways or molecules ginseng exerts its effect on. These range, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(119 citation statements)
references
References 148 publications
(174 reference statements)
4
114
0
1
Order By: Relevance
“…It has been used widely as a tonic for various disorders in China, Korea and Japan for over two thousand years and is now a popular herbal remedy worldwide. Ginsenosides, the bioactive ingredients of ginseng, have been proven to provide therapeutic effects affecting the cardiovascular, endocrine, immune, and central nervous systems [6,7,8,9]. Ginsenosides are generally classified into two categories, namely the panaxadiols and the panaxatriols.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used widely as a tonic for various disorders in China, Korea and Japan for over two thousand years and is now a popular herbal remedy worldwide. Ginsenosides, the bioactive ingredients of ginseng, have been proven to provide therapeutic effects affecting the cardiovascular, endocrine, immune, and central nervous systems [6,7,8,9]. Ginsenosides are generally classified into two categories, namely the panaxadiols and the panaxatriols.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that acupuncture treatment improved the cognitive function of MID rats. (3) Inhibiting the abnormal phosphorylation of Tau protein (Shi et al, 2010;Kim et al, 2013;Li et al, 2015). The studies also found that Ginsenoside Rb1, Rg1, Rd and Icariin can inhibit the abnormal phosphorylation of Tau protein, and some other studies have used electroacupuncture to treat AD rats, the results showed that the total Tau protein levels in the electroacupuncture group were lower than those in the model group, indicating that acupuncture can inhibit the abnormal expression and hyperphosphorylation of Tau protein, reduce the accumulation of neuronal fibrous entanglement in cells, and prevent abnormal Tau entanglement spreading from the inner olfactory cortex to the cerebral cortex and hippocampus .…”
Section: Acupuncture Plus Herbal Medicine For Alzheimer's Disease 1339mentioning
confidence: 99%
“…Rh2가 있으며, PPT계는 Re, Rg1, Rg2, Rf, Rh1, F1으로 분 류되며 3) , in vitro 연구에서 Rh1은 활성산소를 억제하는 항 산화작용을 한다고 보고되었고 [4][5][6] , Rb2는 암독소 호르몬에 대한 길항작용이 있다고 보고되었다 7,8) . Fig.…”
unclassified